ANALYSIS OF CLIMATE AND VAPOR PRESSURE DEFICIT (VPD) IN A HEATED MULTI-SPAN PLASTIC GREENHOUSE - A. Çaylı1 and A.N. Baytorun (Journal of Animal and Plant Sciences, 2021)
One of the most common problems encountered in greenhouse production, i.e., high humidity, provides a favorable environment for the development of various diseases, thereby leading to significant reduction in product quality and quantity. The humidity in a greenhouse for plant growth is expressed via the vapor pressure deficit (VPD), which is an important indicator of the temperature-dependent moisture content of air. In this study, changes in the temperature-dependent relative humidity (RH) and VPD were investigated for a heated greenhouse growing different plants where is located in the Cevdetiye district of Osmaniye province in the Eastern Mediterranean Region in Turkey. For this purpose, VPD values were calculated by measuring the temperature and RH above and below the thermal screen in each compartment of the greenhouse for two months from December 2018 to January 2019, and the relationships between other climate parameters were determined using regression models. The findings revealed significant differences (P <0.01) between the day and night values in all compartments. Pepper, eggplant-cucumber, and tomatoes were grown in three separate greenhouse compartments with the same structural characteristics and heating at night. The number of VPD values lower than the comfort limit was compared with the total number of measurements that were performed hourly. Values of 4.4%, 43.5%, and 36.8% (nighttime) and 3.4%, 23.6%, and 27.3% (daytime) were obtained for the greenhouses containing pepper, eggplant-cucumber, and tomatoes, respectively.
Keywords: Greenhouses; Vapor pressure deficit; VPD; Greenhouse heating; Greenhouse climate